Vaccines for African swine fever: an update - Zhang, Hongliang; Zhao, Saisai; Zhang, Haojie; Qin, Zhihua; Shan, Hu; Cai, Xiulei (Frontiers in Microbiology, 2023)
African swine fever (ASF) is a fatal infectious disease of swine caused by the African swine fever virus (ASFV). Currently, the disease is listed as a legally notifiable disease that must be reported to the World Organization for Animal Health (WOAH). The economic losses to the global pig industry have been insurmountable since the outbreak of ASF. Control and eradication of ASF are very critical during the current pandemic. Vaccination is the optimal strategy to prevent and control the ASF epidemic, but since inactivated ASFV vaccines have poor immune protection and there aren’t enough cell lines for efficient in vitro ASFV replication, an ASF vaccine with high immunoprotective potential still remains to be explored. Knowledge of the course of disease evolution, the way of virus transmission, and the breakthrough point of vaccine design will facilitate the development of an ASF vaccine. In this review, the paper aims to highlight the recent advances and breakthroughs in the epidemic and transmission of ASF, virus mutation, and the development of vaccines in recent years, focusing on future directions and trends.